Participatory Design - Henry Sanoff (DEPARCH Journal of Design Planning and Aesthetics Research)
Participatory design is the involvement of people in the creation and management of their built and natural environments. Its strengths are that it cuts across traditional professional boundaries and cultures. The activity of participatory design is based on the principle that the built and natural environments work better if citizens are active and involved in its creation and management instead of being treated as passive consumers. The main purposes of participation are to involve citizens in planning and design decision-making processes and, as a result increase their trust and confidence in organizations, making it more likely that they will work within established systems when seeking solutions to problems; to provide citizens with a voice in planning, design and decision-making in order to improve plans, decisions, service delivery, and overall quality of the environment; and to promote a sense of community by bringing people together who share common goals. A wide range of techniques is available to designers. Some of these techniques have become a standard method used in participatory processes, such as interactive group decision-making techniques that take place in workshops. At the same time, designers have effectively used field techniques such as questionnaires, interviewing, focus groups and group mapping to acquire information. In general, many of the techniques facilitate citizen’s awareness to environmental situations, and help activate their creative thinking. The techniques can be classified as awareness methods, group interaction methods, and indirect methods.